Assessing corporate brand equity of public universities - Shuhaida Md Noor,; Kamaruzzaman Abdul Manan,; Haja Mydin Abdul Kuthoos, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Brand equity studies focus heavily on the brands of profit-based organisations. Similarly in Malaysia, while there have been a number of studies on leading brands owned by profit-based organisations (e.g. Petronas, Air Asia and Maxis), few studies have explored branding in relation to not-for-profit organisations, such as public universities. Public universities tend not to place too high a priority on their brand development because they often lack an understanding of the significance of brand equity. The increased pressure on public universities to compete in the highly competitive higher education market, however, is slowly changing this perception. Therefore, this study will offer some preliminary insights into the dimensions contributing to the corporate brand equity of a public university in Malaysia, Universiti Sains Malaysia (USM). This study illustrates how metrics can be used to assess the brand of a public research university and can facilitate the development of corporate brand equity metric for institutions of higher education. Data collection was conducted using the survey method, distributing questionnaires to 400 students from eight local public universities. The findings of this study indicate that the dimensions of awareness, quality of service, trust and relevance have a positive relationship with USM’s corporate brand equity. These findings may help to guide future researchers in understanding the dimensions of brand equity in relation to public universities.